2015
DOI: 10.3892/br.2015.484
|View full text |Cite
|
Sign up to set email alerts
|

Association of FURIN and ZPR1 polymorphisms with metabolic syndrome

Abstract: Although genome-wide association studies (GWASs) have identified various genes and loci in predisposition to metabolic syndrome (MetS) or each component of this condition, the genetic basis of MetS in individuals remains to be identified definitively. The aim of the present study was to examine the possible association of MetS in individuals with 29 polymorphisms that were previously identified as susceptibility loci for coronary artery disease or myocardial infarction by meta-analyses of GWASs. The study popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 61 publications
(49 reference statements)
1
31
0
Order By: Relevance
“…A point mutation at the insulin pro-receptor processing site, later identified as a furin cleavage site [6], was reported in an individual suffering from extreme insulin-resistant diabetes and resulted in the absence of the proreceptor processing [7]. An association between a polymorphism in the furin gene and decreased triglycerides and increased high-density lipoprotein cholesterol (HDL-C) serum concentration was recently established [8]. Moreover, in a recent epidemiological study, elevated circulating furin levels were demonstrated to be associated with a score for the metabolic syndrome as well as with increased BMI and blood triglyceride concentration [9].…”
Section: Introductionmentioning
confidence: 99%
“…A point mutation at the insulin pro-receptor processing site, later identified as a furin cleavage site [6], was reported in an individual suffering from extreme insulin-resistant diabetes and resulted in the absence of the proreceptor processing [7]. An association between a polymorphism in the furin gene and decreased triglycerides and increased high-density lipoprotein cholesterol (HDL-C) serum concentration was recently established [8]. Moreover, in a recent epidemiological study, elevated circulating furin levels were demonstrated to be associated with a score for the metabolic syndrome as well as with increased BMI and blood triglyceride concentration [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, furin is a major regulator of cardiac functions, via the processing of multiple substrates. Recently, a GWAS revealed that a nucleotide A to C substitution in intron 1 of the FURIN gene (rs17514846) was significantly associated with the development of the metabolic syndrome, with the protective minor A allele correlating with a 21% decreased serum TG (Ueyama et al, 2015). Interestingly, furin inactivates lipoprotein lipase, which is implicated in the hydrolysis of TG into fatty acids from TG-rich lipoproteins (Jin et al, 2005;Lei et al, 2011).…”
Section: B Furin and Ski-1/s1p In Cardiovascular Diseasesmentioning
confidence: 99%
“…1,2 It is associated with endothelial dysfunction, angiogenesis that might lead to increased risk for diabetes mellitus, insulin resistance, and cardiovascular diseases. 3 Ridker et al reported slight increase in moderate C-reactive protein (CRP) levels in relation to the number of MetS components in a follow-up study on healthy American women. 4 CRP consists of five 23 kDa subunits which has a crucial role in the human immune system.…”
Section: Introductionmentioning
confidence: 99%
“…2 Given that CRP is found to have an important role in MetS, the association between polymorphisms of inflammatory marker gene and MetS were studied. 3 Among various gene association studies, one of the most reported genes is CRP. The human CRP gene is on chromosome 1q21-1q23, approximately 1.9 KB, and has two exons, which are linked by a 280 base pair intron.…”
Section: Introductionmentioning
confidence: 99%